Creating a Winning Organisation - Bajracharya, Pushkar; Chapagain, Bal Ram (Administration and Management Review, 2009)
Many companies assume that once they have launched a major innovation, growth will soon follow. But, it is not that simple. This paper provides a framework of critical success factors for creating a winning organization. Study reveals that winners always have a passion for redefining the boundaries, intense curiosity, and vision. They prefer risk taking as opposed to status quo – seeing past as simply historical reference and not holding it too tightly. It notes further, that a winning strategy requires more than benchmarking a strategy that appears to be working for others and simply incorporating it into one’s business plan. Likewise, trusting, empowering and recognizing people’s minds and efforts can have enormous impact on the bottom line. After all, it is the people of the organization who make everything happen. System focus is another imperative aspect to bring synergic effects in organizational performance, and ultimately to exceed customers’ expectations. Above all, winning organizations are the active learners who always search for better ways of doing things. Administration And Management Review Vol 20, No.2 August 2008 Page: 1-10